BUSINESS OPPORTUNITIES SEARCH - Inche Mítma, Jorge Luis (1999)
The search for business opportunities, a process that generally takes place instinctively, sometimes it is as simple as finding new markets; but it is not always so. This article describes the techniques of creativity in the process and information requirements to perform.